Altered threat and safety neural processing linked to persecutory delusions in schizophrenia: a two-task fMRI study. Issue 3 (30th September 2015) - Perez, David L.; Pan, Hong; Weisholtz, Daniel S.; Root, James C.; Tuescher, Oliver; Fischer, David B.; Butler, Tracy; Vago, David R.; Isenberg, Nancy; Epstein, Jane; Landa, Yulia; Smith, Thomas E.; et al.
Abstract: Persecutory delusions are a clinically important symptom in schizophrenia associated with social avoidance and increased violence. Few studies have investigated the neurobiology of persecutory delusions, which is a prerequisite for developing novel treatments. The aim of this two-paradigm functional magnetic resonance imaging (fMRI) study is to characterize social "real world" and linguistic threat brain activations linked to persecutory delusions in schizophrenia ( n =26) using instructed-fear/safety and emotional word paradigms. Instructed-fear/safety activations correlated to persecutory delusion severity demonstrated significant increased lateral orbitofrontal cortex and visual association cortex activations for the instructed-fear vs. safety and instructed-fear vs. baseline contrasts; decreased lateral orbitofrontal cortex and ventral occipital-temporal cortex activations were observed for the instructed-safety stimuli vs. baseline contrast. The salience network also showed divergent fear and safety cued activations correlated to persecutory delusions. Emotional word paradigm analyses showed positive correlations between persecutory delusion severity and left-lateralized linguistic and hippocampal–parahippocampal activations for the threat vs. neutral word contrast. Visual word form area activations correlated positively with persecutory delusions for both threat and neutral word vs. baseline contrasts. This study links persecutory delusions to enhanced neural processing of threatening stimuli and decreased processing of safety cues, and helps elucidate systems-level activations associated with persecutory delusions in schizophrenia. Highlights: Paranoid delusions positively correlated with fear related sensory processing. Paranoid delusions negatively correlated with safety related sensory processing. The salience network showed divergent fear and safety cued activations. Paranoid delusions positively correlated with hippocampal activations. Paranoid delusions correlated with threat word linked language network activations.